Performances of Myanmar Military in COVID-19 Pandemic Period & Disparities of Public Attitudes on Myanmar Military "Between Before COVID-19 And Present COVID-19 Period" - Marnn, Phyoe; Oo, Thaw Tar; Zin, Phyo Moh Moh; Jean Claude, Nizeyimana (Technium Social Sciences Journal, 2021)
COVID-19 is well known as “Global Pandemic” and it is a dreadful disaster on the world. However, on the other hand, COVID-19 pandemic becomes study issues for many researchers and their juniors and followers. Moreover, some negative attitudes of some Myanmar people to Myanmar National Soldiers become positive attitudes of them. Myanmar has many conflicts between some people who stand with NLD (National League for Democracy) and some people who stand with Myanmar Military. On Social Media pages, Myanmar public have quarreled and they are still quarrelling even in public areas and moreover family members become conflicts due to their favorite organization and poor knowledge of politics. Myanmar Tradition was so gentle and polite and polite people of Myanmar never abused other people and they had extremely tolerance each other before social media did not share rumors of Myanmar Military and Government. This conflicts are severe more and more and it is becoming bad situation of unity of Myanmar. Unfortunately, COVID-19 pandemic appeared as global disasters and Myanmar Military was ready to support public by taking their responsibilities. Military Quarantine Centers for public are so systematical and patients and their families don’t need to worry about their medical care services, medicines and their daily meals and moreover for their necessary daily items are ready placed there. COVID-19 is so cruel warfare for every country and on the other hand, this warfare could reform “Unity Damage” of Myanmar. 57% of negative attitudes of some Myanmar people have been decreased. This study aimed to reform “Noble Unity” of Myanmar and some conditions of COVID-19 were recorded to protect fake informations of COVID-19 periods by some social media pages. The researchers hope “Developed Myanmar” with “Noble Unity and Peace”.